Identification of a novel self-sufficient styrene monooxygenase from Rhodococcus opacus 1CP - Tischler, Dirk; Eulberg, Dirk; Lakner, Silvia; Kaschabek, Stefan R; van Berkel, Willem J H; Schlömann, Michael (Journal of bacteriology, 2009)
Sequence analysis of a 9-kb genomic fragment of the actinobacterium Rhodococcus opacus 1CP led to identification of an open reading frame encoding a novel fusion protein, StyA2B, with a putative function in styrene metabolism via styrene oxide and phenylacetic acid. Gene cluster analysis indicated that the highly related fusion proteins of Nocardia farcinica IFM10152 and Arthrobacter aurescens TC1 are involved in a similar physiological process. Whereas 413 amino acids of the N terminus of StyA2B are highly similar to those of the oxygenases of two-component styrene monooxygenases (SMOs) from pseudomonads, the residual 160 amino acids of the C terminus show significant homology to the flavin reductases of these systems. Cloning and functional expression of His(10)-StyA2B revealed for the first time that the fusion protein does in fact catalyze two separate reactions. Strictly NADH-dependent reduction of flavins and highly enantioselective oxygenation of styrene to (S)-styrene oxide were shown. Inhibition studies and photometric analysis of recombinant StyA2B indicated the absence of tightly bound heme and flavin cofactors in this self-sufficient monooxygenase. StyA2B oxygenates a spectrum of aromatic compounds similar to those of two-component SMOs. However, the specific activities of the flavin-reducing and styrene-oxidizing functions of StyA2B are one to two orders of magnitude lower than those of StyA/StyB from Pseudomonas sp. strain VLB120.